Effect of coated graphene on friction and wear properties of nickel-based self-lubricating coatings prepared by laser cladding - Kun Dong; Wenhao Zhang; Zhaoqiang Chen; Haitao Cui; Xiu Zheng; Xiaoyu Mu; Chonghai Xu (Journal of Materials Research and Technology)
Graphene is an ideal material for improving the self-lubricating properties of coatings, but the high-energy laser beam can damage graphene during the laser cladding process. Therefore, in this paper, amorphous silicon dioxide (SiO2) is used to surface coat graphene particles to obtain silica-coated graphene with core-shell structure (G@SiO2). By adding niobium carbide (NbC) as the ceramic reinforcing phase and G@SiO2 nanoparticles as the solid lubricant in Ni60, a self-lubricating composite coating was prepared on the surface of 45 steel matrix by laser cladding technology. It is shown that G@SiO2 can promote the grain refinement of NbC in the coating. On the other hand, the addition of G@SiO2 promotes the generation of hard phase of chromium carbide, which together with NbC improves the hardness of the material. The maximum microhardness of the composite coating was 946 HV, which was 302.7% higher than that of the 45 steel base material. The lowest coefficient of friction value of the coated material was 0.25, and the lowest wear amount was 2.45 × 106 μm3. Compared with the composite coating without added G@SiO2, the coefficient of friction of the coated material with the addition of G@SiO2 was reduced by 50% and wear amount was reduced by 62%.